Religion in the Public Sphere - SOLANGE LEFEBVRE, LORI G. BEAMAN (University of Toronto Press, 2014)
Religion is frequently referenced in relation to its presence or absence from the public sphere, or its relegation to the private sphere. 1 In part, the often easy use of the terms â€œpublicâ€ and â€œprivateâ€ in relation to religion inspired the creation of this volume. Despite the fact that private and public are regularly invoked in discussions about religion, there is little systematic refl ection on the meaning of these terms, specifi cally on the boundaries between them or what, exactly, we mean when we use them. For instance, religion is said to be â€œprivate,â€ or â€œreligion in the public sphereâ€ is identifi ed as requiring discussion. Indeed, one of the fi nal meetings of the Religion and Society Programme, a large research initiative based in the United Kingdom, had as its core theme â€œNew Forms of Public Religion.â€ 2 In 2012, the comparative European project RELIGARE published a collective book on that topic, entitled Religion in Public Spaces : A European Perspective (Ferrari and Pastorelli 2012). Yet, scholarly refl ection on what it means to link or distinguish between â€œreligionâ€ and â€œpublicâ€ and â€œprivateâ€ remains relatively rare outside of specifi c and isolated contexts. Thus, we frequently see reference to the idea of religion being â€œprivatizedâ€ or â€œpushed to the private sphere,â€ but little refl ection on where the boundaries of the private sphere are. It seems that the public/private distinction has become essential to any discussion on religion. The chapters in this volume show how subtle, complex, and changing the frontier between the two can be. Religion has become the subject of frequent and lively debate in a wide range of places: in the media; among academics, policy makers, and communities; and within social institutions. This increase in attention has resulted in a reconsideration of religion and its place in society, raising the question of whether religion is enjoying a resurgence.